My grandfather's son : a memoir - Thomas, Clarence, 1948- (New York : Harper, 2007)
The Supreme Court justice recounts his life story, from his impoverished childhood in Jim Crow-era Georgia and his struggles to acquire an education, to his publicly contested confirmation to the nation's highest court.
Sun to sun -- As good as us -- The corridor -- No room at the top -- The golden handcuffs -- Question of will -- "Son, stand up" -- Approaching the bench -- Invitation to a lynching -- Going to meet the man.
Keywords: Thomas, Clarence, -- 1948-; United States. -- Supreme Court -- Officials and employees -- Biography; African American judges -- Biography; Thomas, Clarence, -- 1948-; Judges -- United States -- Biography; United States. -- Supreme Court -- Officials and employees -- Biography; African American judges -- Biography; Thomas, Clarence